Research on Tunnel Lining Cavity Treatment Technology of a Metro Tunnel in Chongqing. Issue 3 (September 2019) - Hu, Xuebing; Jiang, Xinghong; Li, Ke; Cui, Xiangyang
Abstract: The hollowing problem of tunnel lining structure is like a suspended bomb, which may affect the safety of vehicles and the safety of passengers at any time. Therefore, the study of tunnel lining structure cavity management technology has great social significance for ensuring tunnel safety. Taking a metro tunnel in Chongqing as an example, this paper proposes a reasonable lining structure reinforcement scheme of changing partial arches and reinforcing by steel strips after analyzing the environment, the bearing requirements, and the size and location of cavities. Based on the calculation formula of flexural members given by Code for Design of Concrete Structure Reinforcement, reduction system is introduced to calculate safety coefficient of flexural and compression members. The minimum value of structural bearing after treatment is 4.4, which meets the requirement of bearing capacity. Stratum structure method is used to calculate surrounding rock deformation during reinforcement. The maximum horizontal displacement is 1.9 mm, and the vertical displacement is 6 mm. The surrounding rock could be stable when treating defects, and the treatment scheme meets the requirements of bearing capacity and inner clearance. Therefore, the tunnel lining structure cavity can be reinforced by means of shotcrete and steel strips, without interrupting traffic and ensuring driving safety. The success of the treatment provides a useful reference for other similar projects.